DIGITAL CONTENT STRATEGY OF CURATION HOUSE THROUGH LANDING PAGE IN INCREASED BUYING INTEREST - Chiya Ratul Umah (Universitas Catur Insan Cendekia (CIC) Cirebon, 2024)
AbstractThe world of digital technology has been growing, one of which is the field of digital marketing. One of the sectors most affected by this technological development is the economic sector, especially MSME players. MSMEs must be able to keep up with the rapid development of technology. Digital content is one of the digital marketing strategies that can be implemented by MSMEs. One digital platform that is actually easy to utilize is the landing page. Product curation is needed in order to find out the weaknesses and advantages of a product, both in terms of products, management and marketing. Rumah Kurasi is present in the midst of MSMEs with experts / expert curators in it as a new breath. This study aims to determine the effect of digital content strategy through landing pages by Rumah Kurasi on increasing product demand. The research method used in this research is descriptive qualitative with the type of field research. Data sources come from primary data sources obtained from interviews and participatory observations. Secondary data sources come from the official website of Rumah Kurasi. The data analysis technique used is data reduction, data presentation and final conclusion drawing. The results of this study show that landing pages can be utilized by MSME actors as a medium for product promotion as an effort to increase consumer buying interest in products. The real strength of the landing page is the content that is put into it. The better and better the content entered, the more interested visitors will be and the easier it is to take action on the advertisements posted.Keywords: Digital Content, Landing Page, and Purchase Intention